Risk Factors for Gastrointestinal Symptoms post Enteral Nutrition Initiation via a Gastrostomy Tube - Yusaku Kajihara (The Indonesian Society for Digestive Endoscopy, 2020)
Background: Percutaneous endoscopic gastrostomy (PEG) facilitates long-term enteral nutrition. However, parenteral nutrition prior to PEG tube placement can cause impaired gastrointestinal function. Additionally, upon initiation of enteral feeding via a PEG tube, some patients suffer from gastrointestinal symptoms (e.g., vomiting, diarrhea), which reduce their quality of life and increase the nursing workload.Method: This retrospective study included 155 patients upon whom the author performed PEG as the attending physician. Enteral nutrition was started through the PEG tube on the third day after its placement. The following characteristics were analyzed: age, gender, indications for PEG, preoperative enteral nutrition, administered liquid nutrients, daily dosage of nutrients, serum albumin levels, serum alanine aminotransferase levels, serum creatinine levels, serum hemoglobin levels, and vomiting or diarrhea within seven days after the initiation of PEG feeding. A logistic regression model was used to identify the risk factors contributing to gastrointestinal symptoms, and three variables were sequentially introduced into the model—preoperative non-enteral nutrition, hypoalbuminemia, and administration of non-elemental diets.Results: Vomiting and diarrhea occurred in 10 and 15 patients, respectively. There were significant differences in administered nutrients and serum albumin levels between patients with and without gastrointestinal symptoms. Multivariate analysis revealed that the adjusted odds ratios for administration of non-elemental diets and serum albumin level ≤3.2 g/dL were 8.05 (95% confidence interval (CI): 2.66–24.4; p 0.001) and 3.81 (95% CI: 1.33–10.9; p 0.05), respectively.Conclusion: The administration of non-elemental diets and a serum albumin level ≤3.2 g/dL were significant risk factors.